The Influence of Social Media Marketplace Affiliates on Purchasing Decisions for Fashion Products - Lathifah, Ummi; Prabawati, Melly; Arrsyi, Esty Nurbaity (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2024)
This study aims to determine the influence of social media marketplace affiliates on purchasing decisions for fashion products. This research uses a survey method with a quantitative approach and an associative research design. The population in this study consists of consumers aged 18–34 years in the JABODETABEK area who have purchased fashion products through marketplace affiliate links. The sampling technique used in this study is non-probability sampling with the incidental method, resulting in a sample size of 100 people. Data collection was carried out using a questionnaire with a Likert scale. The analysis technique used is the chi-square test. The results showed an Asymp. Sig. Pearson Chi-Square of 0.001 with a significance value of p = 0.001 (p 0.05). It can be concluded that there is a significant influence of social media marketplace affiliates on purchasing decisions for fashion products.